Investigating the effect of in vitro gastrointestinal digestion on the stability, bioaccessibility, and biological activities of baobab (Adansonia digitata) fruit polyphenolics. (June 2021) - Ismail, Balarabe B.; Guo, Mingming; Pu, Yunfeng; Çavuş, Osman; Ayub, Khadijah Abdulkadir; Watharkar, Ritesh Balaso; Ding, Tian; Chen, Jianchu; Liu, Donghong
Abstract: Baobab ( Adansonia digitata ) fruit had received growing attention for its myriad nutritional and medicinal benefits, including those from its polyphenol-rich profile and powerful antioxidant activity. The current study evaluated the bioaccessibility of phenolic constituents and antioxidant capacity of baobab fruit pulp (BFP) and its byproduct, the baobab fruit shell (BFS), upon in vitro digestion. In general, the in vitro digestion reduced phenolic contents and antioxidant capacity; however, several flavonoids, particularly quercetin, proanthocyanidin, proanthocyanidins B1 and B2 were highly bioaccessible. Specifically, a significant increase in the bioaccessibility of proanthocyanidins (173%) in BFS was observed following gastric digestion, possibly due to hydrolysis of proanthocyanidin isomers. Moreover, a significantly higher bioaccessibility of proanthocyanidin B2 (170%) and quercetin (304%) in BFP, and proanthocyanidin (363%) in BFS was also observed following intestinal digestion probably due to pancreatin effect on the complex food matrix or the depolymerisation of insoluble proanthocyanidin and quercetin conjugates induced by the increase in pH. A considerable α-amylase and α-glucosidase inhibition in all samples (>50% inhibition) were observed following the in vitro digestion. Hence, both BFP and BFS are good sources of bioaccessible polyphenolics that could be utilised as ingredients in functional foods. Highlights: Baobab fruit pulp and its byproduct were subjected to in vitro digestion. The digestion has a reducing effect on phenolic constituents and antioxidant capacity. Gastric and intestinal digestion steps increased proanthocyanidins bioaccessibility. A considerable α-amylase and α-glucosidase inhibitory activity was achieved. Techniques such as microencapsulation could be used to increase bioaccessibility.